Engine Performance and Emission of Emulsified Biodiesel - Amir, Aziz; Ahmad Fitri, Yusop; R., Mamat (2014)
An emulsion of biodiesel and water is one of the possible approaches that have been used to overcome diesel engine pollution. In this work, the performance and emission characteristics of a 4-cylinder diesel engine using pure diesel, biodiesel B20 and emulsified biodiesel were investigated. Emulsified biodiesel containing 5 % and 10 % water were utilize for the engine tests. During the experimental work, the engine was set-up at 2500 rpm and 20 % to 60 % loads. The result shows the reduction in NOx formation when the water content in emulsified biodiesel increased from 5 % to 10%. For the performance, there were no significant differences between the engine break powers measured for emulsified biodiesel containing 5% water and diesel fuel.